A study of phosphorus dynamics in the main basin of Swartvlei, September - December 1980 - Silberbauer, M J (Rhodes University, Faculty of Science, Department of Geology, 1981)
Introduction: Phosphorus is an especially scarce element in the aquatic environment, yet it is of vital importance to living organisms: the pyrophosphate bond is the basis of biochemical energy transfer, and phosphate groups make up the backbone of the nucleic acids (Wetzel, 1975). An understanding of phosphorus movements and transformations is thus essential to a study of the biological functioning of a lake. The present report describes a study of phosphorus dynamics inSwartvlei, a lake with an extremely low pelagic primary production rate, in the order of 0,15 gC.mâ »Â².dâ »Â¹ (Robarts, 1973; Howard-Williams and Allanson, 1978). The littoral phosphorus dynamics of Swartvlei have been discussed in some detail (Howard-Williams, 1977; Howard-Williams and Allanson, 1978), and what follows is an attempt to quantify the changes in phosphorus concentration occurring in the deeper parts of the lake, which comprise some 57% of the total area.
Keywords: Phosphorus -- Environmental aspects -- South Africa -- Swartvlei; Lakes -- South Africa -- Swartvlei; Limnology -- South Africa -- Swartvlei; Aquatic ecology -- South Africa -- Swartvlei